Historical Aspects of the Institute of Evidence and Proof in Civil Proceedings in Latvia (1918–1940) - Jurkeviča, Tatjana (Teisė, 2022)
The institute of evidence is an integral part of achieving the objectives of civil proceedings, and only through it can effective civil protection be ensured in the courts. Within the framework of this paper, the concept and essence of evidence, as well as the general rules of proof in Latvia in the period from 1918 to 1940, are studied.
Keywords: theory of evidence; evidence and proof; Latvian law; civil proceedings; First Independence of Latvia